MENINGKATKAN KREATIVITAS DAN KEWIRAUSAHAAN ANAK SEJAK DINI DI ISTANA PANTI ASUHAN AL-JUFRI BATAM - Nolla Puspita Dewi; Faris Ramadhan; Mursal Mursal; Liyana Khairunnisa Fawwaz; Liana Liana (LPPM Universitas Bina Bangsa, 2024)
The development of the creative economy cannot be separated from the younger generation as a treasure of creativity. A creative idea that can spread entrepreneurship and support the government's efforts in reducing unemployment in Indonesia. This study aims to analyze Increasing Children's Creativity and Entrepreneurship Early at the Palace of Al-Jufri Orphanage Batam. Today's young generation is less able to utilize their productivity and creativity well. There are still many young people who commit crimes from an early age. Therefore, students need to equip them by exploring creative ideas in themselves that can be directed to the business world. Where this young entrepreneur can make the development potential both in number and quality in his own entrepreneur. With the Community Service Program aimed at the Children of the Orphanage